THE INFLUENCE OF GENDER DIVERSITY AND INTELLECTUAL CAPITAL ON COMPANY PERFORMANCE IN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) MEDIATION (STUDY ON BUMN COMPANIES 2015-2022) - Dunya, Muhamad Abi; Bastian, Elvin; Soleha, Nurhayati (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research aims to examine the influence of gender diversity and intellectual capital on company performance in environmental, social and governance (ESG) mediation. The object of this research is state-owned companies listed on the Indonesian Stock Exchange for the period 2015-2022. This research used quantitative descriptive methods and purposive sampling techniques for sampling so that 177 research samples were obtained. The data analysis used in this research is multiple linear regression and path analysis using the Eviews 10 software tool. The results of this research show that Gender Diversity has no influence on Environmental, Social, Governance (ESG) and Intellectual Capital has an influence on Environmental, Social, Governance (ESG). Then Gender Diversity has no influence on Company Performance. Intellectual Capital has an influence on Company Performance, and Gender Diversity has no influence on Company Performance and is mediated by Environmental, Social, Governance (ESG). Intellectual Capital has an influence on Company Performance and is mediated by Environmental, Social, Governance (ESG).